Spider communities in urban green patches and their relation to local and landscape traits - Argañaraz, Carina Inés (2018)
Urbanization and urban landscape characteristics greatly alter plant and animal species richness and abundances in negative and positive directions. Spiders are top predators, often considered to be sensitive to habitat alteration. Studies in urban environments frequently focus on ground-dwelling spiders or on spiders in built structures, leaving aside foliage spiders. Effects of habitat, landscape type and structure and local characteristics on spider species composition, richness and relative abundance were evaluated in urban green patches in a temperate city of South America. We also assess whether Salticidae could be an indicator group for the broader spider community in the urban environment. Spiders were sampled with a G-VAC (aspirator) in urban green patches in Córdoba city, Argentina, in urban, suburban and exurban habitats (18 sites; six per habitat) and local and landscape traits were assessed. Overall, the exurban was richer than the urban habitat, however, at the site level Salticidae richness and abundance (but not the total spider assemblage) were significantly lower in urban sites. Species composition moderately differed between urban and exurban sites. Results indicate that on urban green spaces a low impervious surface cover, a coverage of trees, herbaceous vegetation and a vertical structure of vegetation at least up to 1m in height contribute to higher richness and abundance of spiders, Salticidae being more sensitive than the overall spider community to local effects. In addition, Salticidae richness can predict 74% of the total spider richness recorded and may be used as spider diversity bio-indicators in this climatic region.